Effect of Weather Conditions to Vascular Streak Dieback Disease Severity on Some Cocoa Clones with Different Resistant Levels - Aini, Febrilia Nur; Aini, Luqman Qurata; Syibli, Muhammad Akhi; Sari, Indah Anita; Susilo, Agung Wahyu; Setyawan, Bayu; Malik, Abdul; Budiman, Aris (Research Journal of Life Science, 2023)
Vascular streak dieback is a major disease in cocoa trees that affects at in various stages, and effect in significant yield losses. This study aimed to identify the area under the disease progress curve (AUDPC), infection rate (r), and the influence of weather factors on the development of vascular streak dieback disease caused by Ceratobasidium theobromae in some cocoa clones with different resistant levels. The research used a randomized complete block design consisted six clones as treatment and each treatment consisted of three replications. Disease severity was observed on six different cocoa clones and observations were conducted monthly. The observation of disease severity was observed monthly for 12 months and then used to analyze AUDPC and infection rate. Monthly data on the weather conditions were taken from the climatology station of the Indonesian Coffee and Cocoa Research Center, East Java. The results showed that Sulawesi 01 and ICCRI 09, categorized as resistant clones, showed low AUDPC values, 0.02 and 2.85 respectively. The cocoa clones Sulawesi 02 and MCC 02, categorized as tolerant clones, had higher AUDPC values, 19.87 and 34.27 respectively. The cocoa clones BCL and BL 50 showed the highest AUDPC values, 277.05 and 265.70 respectively. Path analysis on resistant clones indicated that rainfall is the most influential weather factor in increasing the severity of vascular streak dieback, followed by temperature. Higher relative humidity can significantly reduce disease severity, while sunlight and wind speed have smaller effects. In contrast, path analysis on susceptible clones showed that temperature, rainfall, relative humidity, and wind speed all positively influence the severity of vascular streak dieback. At the same time, sunlight has a mitigating effect.